Purification, characterization of mosquito larvicidal lectin from Annona muricata and its eco-toxic effect on non-target organism. (December 2020) - Parthiban, Ezhumalai; Arokiyaraj, Charles; Janarthanan, Sundaram; Ramanibai, Ravichandran
Graphical abstract: Highlights: The lectin was successfully purified from Annona muricata had MW of 260 kDa. Annona muricata lactin had high pH and thermal stability. Soursop lectin had maximum homology with leguminous plant lectin. Potent mosquito larvicidal activity of soursop lectin was noted to Aedes aegypti . The lectin causes a low toxicity level on non-target larvae, Chironomous costatus . Abstract: The present study investigates the purification and characterization of mosquito larvicidal lectin from the seed kernel extract of Annona muricata and toxic effects on non-target organism Chironomus costatus . Soursop lectin was purified by anion-exchange column chromatography using DEAE-cellulose with approximately molecular mass of 260 kDa and with seven distinct subunits (16, 18, 21, 22, 24, 73 and 95 kDa). Soursop lectin highest Hemagglutination (HA) titer value of 128 was recorded against hen indicator RBC type with the influence of different divalent cations such as Ca 2+, Ba 2+ and Mn 2+ . The lectin mediated HA activity was highly inhibited by monosaccharides of glucose and mannose and disaccharides such as trehalose and melibiose. It was found to be EDTA sensitive (at 30 mM), pH-dependent (between 6–9) and heat-labile (upto 60 °C). A significant homology for soursop lectin was recorded to leguminous seed lectin from Psophocarpus scandens in MALDI-TOF-MS analysis with 66 % of sequence coverage. Finally, the toxicity bioassay of soursop lectin resulted in 100 % larval mortality for A. aegypti at 48 h whereas only 10 % mortality recorded to non-target organism C. costatus . Therefore, we concluded that soursop lectin could be a potent insecticidal agent in integrated pest management for controlling various insect pests.